Dose‐dependent glucosuria of DWP16001, a novel selective sodium–glucose cotransporter‐2 inhibitor, in healthy subjects. Issue 9 (22nd April 2022) - Hwang, Jun Gi; Lee, SeungHwan; Huh, Wan; Han, Jumi; Oh, Jaeseong; Jang, In‐Jin; Yu, Kyung‐Sang
Abstract : Aims: DWP16001 is a novel sodium–glucose cotransporter‐2 inhibitor under development for the treatment of type 2 diabetes mellitus. This study was conducted to evaluate the pharmacokinetics, pharmacodynamics and safety of DWP16001 after single and multiple doses in healthy subjects. Methods: A randomized, double‐blind, placebo‐ and active‐controlled, single‐ and multiple‐dose study was conducted. Twelve subjects in each dose group received a single dose (0.2, 0.5, 1.0, 2.0 or 5.0 mg) or multiple doses (0.1, 0.3, 0.5, 1.0 or 2.0 mg once daily for 15 consecutive days) of DWP16001, dapagliflozin 10 mg or placebo at a ratio of 8:2:2. Serial blood and interval urine samples were collected for the pharmacokinetic and pharmacodynamic analyses. The safety and tolerability of DWP16001 were also assessed. Results: A dose‐dependent increase in the urinary glucose excretion was observed after a single dose, and the steady state urinary glucose excretion was 50–60 g/d after multiple doses in the dose range of 0.3–2.0 mg. DWP16001 was rapidly absorbed with the time to peak plasma concentration of 1.0–3.0 hours, and it exhibited a mean elimination half‐life of 13–29 hours. The systemic exposure to DWP16001 increased proportionally with multiple dose administrations in the range of 0.1–2.0 mg. DWP16001 was well tolerated in all dose groups. Conclusion: DWP16001 induced glucosuria in a dose‐dependent manner, and systemic exposure was observed after multiple doses. DWP16001 was well tolerated in single oral doses of up to 5.0 mg and in multiple oral doses of up to 2.0 mg.